Role of Drug Discovery in Central Nervous System Disorders: An Overview - Mohit Gupta; Ravi Shekhar; Jagdish K Sahu (Current Research in Pharmaceutical Sciences, 2021)
Central nervous system (CNS) stimulants are drugs, which produce a response that could be used to alleviate a particular medical condition. These are the agents, which speed up to treat conditions characterized by lack of adrenergic stimulation, including narcolepsy and neonatal apnea. The majority of CNS stimulants is chemically similar to the neurohormone norepinephrine and simulates the traditional "fight or flight" syndrome associated with sympathetic nervous system arousal. A small figure of added members of the CNS stimulant class do not fall into definite chemical groups. The review on central nervous system stimulants gives detail study of CNS stimulant drugs, their mechanism of action and in vivo models of CNS stimulants.The brain is a delicate tissue, and advancement built very effective methods to guard it. Unfortunately, the same mechanisms that protect it against intrusive chemicals can also upset therapeutic interventions. Many current medications are rendered unsuccessful in the treatment of cerebral maladies due to our incapability to efficiently deliver and sustain them within the brain.